Rebuilding airline networks in the post-COVID-19 era: new network configurations in Europe? - Fontanet-Pérez, Pol; Suau-Sanchez, Pere; Vázquez, Xosé H (Emerald, 2024)
After the standstill generated by theCOVID-19 outbreak, airlines were forced to adapt their operations and strategies to the new market requirements and constraints both in terms of supply and demand. The initial recovery included many short-term decisions for survival. Yet, as the market recovered, sometimes in new forms, airlines rebuilt their networks for a new long-term future. In this chapter, we compare the pre- and postpandemic network configurations of a selection of European airlines using a combination of network structure, topology, and connectivity indicators, which help understand airlines’ network economics. As a general trend, low-cost carriers recovered faster than full-service ones, in many cases already exceeding prepandemic supply volumes. However, our study shows the high heterogeneity of responses and postpandemic network structures across business models.While some airlines kept very similar structures, adapting to the demand change, some opted for a bolder strategy, growing their networks compared to prepandemic levels. Also, in some cases, new regulations or other external events forced the changes in networks. Finally, although in 2022 data still showed long-haul markets a little behind compared to prepandemic figures, signs such as the continued passenger increase and the ramp up of aircraft orders by airlines point toward a full recovery leading back to a sector based on continued traffic growth.
Keywords: 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; Infectious Diseases